Roles of singlet oxygen and triplet excited state of dissolved organic matter formed by different organic matters in bacteriophage MS2 inactivation - Rosado-Lausell, S.; Wang, H.; Gutiérrez, L.; Romero-Maraccini, O.; Niu, X.; Gin, K.; Croué, Jean-Philippe; Nguyen, T. (IWA Publishing, 2013)
Inactivation of bacteriophage MS2 by reactive oxygen species (ROS) and triplet excited state of dissolved organic matter (3DOM*) produced by irradiation of natural and synthetic sensitizers with simulated sunlight of wavelengths greater than 320nm was investigated. Natural sensitizers included purified DOM isolates obtained from wastewater and river waters, and water samples collected from Singapore River, Stamford Canal, and Marina Bay Reservoir in Singapore. Linear correlations were found between MS2 inactivation rate constants (kobs) and the photo-induced reaction rate constants of 2,4,6-trimethylphenol (TMP), a probe compound shown to react mainly with 3DOM*. Linear correlations between MS2 kobs and singlet oxygen (1O2) concentrations were also found for both purified DOM isolates and natural water samples. These correlations, along with data from quenching experiments and experiments with synthetic sensitizers, Rose Bengal (RB), 3'-methoxyacetophenone (3'-MAP), and nitrite (NO2-), suggest that 1O2, 3DOM*, and hydroxyl radicals (•OH) could inactivate bacteriophage MS2. Linear correlations between MS2 kobs and Specific Ultraviolet Absorption determined at 254nm (SUVA254) were also found for both purified DOM isolates and natural samples. These results suggest the potential use of TMP as a chemical probe and SUVA254 as an indicator for virus inactivation in natural and purified DOM water samples.